Analisis Potensi Angin di Kecamatan Mojolaban Berbasi Internet of Things (IoT) - Jevri Ardianto; Taufik Wisnu Saputra; Danar Susilo Wijayanto (Nozel : Jurnal Pendididikan Teknik Mesin, 2025)
This research aims to (1) measure the IoT-based wind potential using wind speed and direction data collected through microcontrollers at heights of 6, 8, 10, and 12 meters; (2) determine the wind potential based on wind speed and direction in Mojolaban Sub-district; and (3) identify suitable wind turbine recommendations that align with the measurement area's conditions. The research was conducted using an experimental method. The data sources for this study include wind speed and direction measured using IoT-based microcontrollers. Purposive sampling was used for sample collection. The instruments used for data collection include anemometers for measuring wind speed and wind vanes for determining wind direction. Validation techniques involved using anemometers and compasses. The data analysis was performed using descriptive quantitative analysis. The research results indicate that the highest average wind speed occurs at a height of 12 meters. Mojolaban Sub-district has an average wind speed of 0.75 m/s, with the dominant wind direction from the north, and a maximum speed of 3.43 m/s. The wind potential in that area is not sufficiently high to be effectively utilized as a significant wind energy source due to its low level and insufficient magnitude. Vertical Savonius wind turbines are a suitable choice for harnessing low wind speeds in Mojolaban Sub-district.